(untitled) (Research, Society and Development, 2021)
The aim of the study was to investigate the perception of caregivers of children with cleft lip and palate regarding the surgical procedure and postoperative care. This is a descriptive, exploratory research, with qualitative data analysis performed according to the Content Analysis methodology proposed by Bardin. Data collection was performed through interviews with caregivers during the multiprofessional preoperative consultation. The data collection instrument contained eight questions to characterize the sample (age, sex, education, family income, degree of kinship of the informant, type of cleft, association with genetic syndrome and surgical procedure submitted) and three questions that sought to explore the doubts , expectations, feelings and sensations related to the surgical procedure. Answers to open questions were recorded and later transcribed by the researchers. The interviewed caregivers showed doubts about the surgical procedure and postoperative care and fear about the outcome, however, it was possible to observe that there was trust in the team, which may be related to the bond generated since the arrival of these patients at the service. It is concluded that the negative feelings of the interviewed caregivers were generated due to anxiety and uncertainties regarding the surgical procedure. Therefore, the importance of multidisciplinary guidelines and the establishment of bonds with patients and their families is highlighted.